Assessing social capital in community forest management in the Mount Hamiding Protection Forest, North Halmahera District, North Maluku, Indonesia (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Kailola J, Purwanto RH, Sumardi, Faida LRW. 2023. Assessing social capital in community forest management in the Mount Hamiding Protection Forest, North Halmahera District, North Maluku, Indonesia. Biodiversitas 24: 431-440. The success of forest management in the context of community forestry cannot be separated from the contribution of social capital. The Mount Hamiding Protection Forest is administratively located in North Halmahera District, North Maluku Province, Indonesia, and has a high biodiversity value with endemic flora and fauna. However, the management has not shown significant impacts in enhancing the welfare of the surrounding community, and there have been forest disturbances due to anthropogenic activities and vertical conflict. Hypothetically, the high level of social capital can support sustainable forest management and improve people's welfare, yet this has not been tested in the context of Mount Hamiding Protection Forest. Therefore, this research aimed to assess the social capital in community forest management in the Mount Hamiding Protection Forest. The quantitative survey was conducted in six villages in North Halmahera District, namely Wangongira, Efi-Efi, Mamuya, Togawa, Soakonora, and Roko. The elements of social capital assessed were trust, social norms, and social networks. The results showed that the level of community trust in the study area's six villages is in the medium category. However, the trust in the internal community is high, and trust in external stakeholders is medium. The communities in the six villages have overall high social norms. The social networks are high in Togawa, Soakonora, and Roko Villages, while the remaining villages have social networks in the medium category. Generally, the community around the Mount Hamiding Protection Forest area has a moderate social capital category due to a lack of participation and trust in written rules and government institutions. Therefore, the Forest Management Unit of North Halmahera District should strengthen the community's social capital to increase knowledge and understanding of written rules, trust in institutions, and network development through organization and participation.
Keywords: Community forestry, protected forest, social capital